Parent Perspective Based on Salary Level of Intrapersonal Intelligence Child Through Sleeping Companions - Tanjung, Salsabila Hasiana; Suparno, S.; Kamtini, K. (Universitas Muhammadiyah Surakarta, 2018)
Education with affection will shape the intrapersonal intelligence of the child the better also. Personality of children in adulthood in general is the formation ofpersonality and education obtained by children through the people around him, especially the family.Activities of storytelling is done before bed can also be said hypnoparenting which is education done at the time of the child before bed. At that time, the child will easily receive an education packed with stories containing advice. Education by way of telling stories to advise on children has been done by parents of ancient times.This study was conducted by giving a questionnaire and conducting simple interviews to randomly selected parents regardless of the background of their lives except the amount of salary they earn each month.This research uses quantitative descriptive method by interviewing selected fifty randomly selected parents. That parents who earn salary at point A or with income Rp 500,000 - Rp 2,000,000 more often accompany child sleep and assume it is important for children with the reason his son still want to be accompanied sleep and feel like accompany the child to sleep because it has been working all day outside.